2015
DOI: 10.1002/ejlt.201400276
|View full text |Cite
|
Sign up to set email alerts
|

Cold pressed capia pepperseed (Capsicum Annuum L.) oils: Composition, aroma, and sensory properties

Abstract: In this study, cold press‐produced capia pepperseed oil samples were characterized. Pre‐roasting and enzyme treatment against control group (no pre‐treatment) were applied to the seeds prior to cold pressing, and the oil yield, meal, and oil quality parameters were examined. The physico‐chemical parameters (refractive index, viscosity, turbidity, specific gravity, color, free acidity, peroxide and iodine values, antioxidant capacity, total phenolic content, and energy value), components composition (fatty acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 19 publications
(51 reference statements)
5
37
0
Order By: Relevance
“…Cold-Pressed Refined-Winterized and we would not suggest it for cold pressed oils. Similar consumer responses to cold pressed capia pepper seed oil (Yılmaz et al, 2015a) and tomato seed oil (Yılmaz et al, 2015b) were observed in our laboratory.…”
Section: Consumer Acceptancesupporting
confidence: 84%
See 3 more Smart Citations
“…Cold-Pressed Refined-Winterized and we would not suggest it for cold pressed oils. Similar consumer responses to cold pressed capia pepper seed oil (Yılmaz et al, 2015a) and tomato seed oil (Yılmaz et al, 2015b) were observed in our laboratory.…”
Section: Consumer Acceptancesupporting
confidence: 84%
“…Strecker et al, (1996) Table 1. Free fatty acidity (FFA) of CPCO was 1.16 %, and higher than that of the RWCO (0.23 %), but this can be considered quite low compared to other cold pressed oils (Yılmaz et al, 2015a;Yılmaz et al, 2015b). The measured acid values are in accordance with the FFA values as well.…”
Section: Physicochemical Propertiessupporting
confidence: 55%
See 2 more Smart Citations
“…The viscosity of the oil was 52.094 cP. Yılmaz et al reported a viscosity of 44.96 cP for oil obtained from the roasted seed of capia pepper. In another study, a viscosity of 25.6 cP was determined .…”
Section: Resultsmentioning
confidence: 99%